Analisis Strategi Pemasaran Produk Skincare Sr12 Pada PT. Xyz - Irene Rizda Septiani Aprizal; Rizqi Novita Sari (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Skincare is a product that has changed many aspects of people's lives in the development of science and technology. The rise of skincare products allows competition to emerge with other similar skincare products. Therefore, a business actor carries out various kinds of promotions and uses good strategies to get the right target consumers. PT. XYZ is a company operating in the creative industry sector. Where in marketing its products PT. XYZ mostly uses digital platforms. However, the promotions that have been carried out so far do not yet know the strengths, weaknesses, opportunities and threats that the company has in order to be able to compete with other companies. Observing these problems, research was carried out to provide solutions through observation and active participation approaches. The research results show that product marketing strategy analysis using the SWOT method can help companies identify strengths, weaknesses, opportunities and threats in order to increase company value